The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40249-017-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

Different challenges, different approaches and related expenditures of community-based tuberculosis activities by international non-governmental organizations in Myanmar

Abstract: BackgroundInternational non-governmental organizations (INGOs) have been implementing community-based tuberculosis (TB) care (CBTBC) in Myanmar since 2011. Although the National TB Programme (NTP) ultimately plans to take over CBTBC, there have been no evaluations of the models of care or of the costs of providing CBTBC in Myanmar by INGOs.MethodsThis was a descriptive study using routinely-collected programmatic and financial data from four INGOs during 2013 and 2014, adjusted for inflation. Data analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The lost-to-follow-up rate of only 3% in our intervention group was much better than the approximately 8% and 10% rates described in the Riyadh [2] and Karachi [23] studies. Some other studies reported a lost-to-follow-up rate of 8–15% [30] , [31] . Bronner et al [30] and Santha et al [32] even reported a rate of 23% and 32% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The lost-to-follow-up rate of only 3% in our intervention group was much better than the approximately 8% and 10% rates described in the Riyadh [2] and Karachi [23] studies. Some other studies reported a lost-to-follow-up rate of 8–15% [30] , [31] . Bronner et al [30] and Santha et al [32] even reported a rate of 23% and 32% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They report that this intervention has been sustained for 8 years due to the collaborative work of the education center, public health department, and the Rochester Healthy Community Association, whose mission is to promote health through a CBPR approach. On the other hand, Han et al (55) conducted a descriptive study in which they mention that a community-based tuberculosis prevention program has greater potential for sustainability by training CHW to form social mobilization working groups that they can train more volunteers and allow the program to be maintained through the years. Therefore, community participation has been shown to lead to significant changes in tuberculosis control.…”
Section: Discussionmentioning
confidence: 99%
“…They report that this intervention has been sustained for 8 years due to the collaborative work of the education center, public health department, and the Rochester Healthy Community Association, whose mission is to promote health through a CBPR approach. On the other hand, Han et al [62] mention that community tuberculosis prevention programs can be sustained over time when CHWs are trained and social mobilization groups are formed. Considering this evidence, community participation has been shown to lead to significant changes in ending tuberculosis.…”
Section: Discussionmentioning
confidence: 99%